1996
DOI: 10.1210/jcem.81.11.8923844
|View full text |Cite
|
Sign up to set email alerts
|

Studies of 3 beta-hydroxysteroid dehydrogenase genes in infants and children manifesting premature pubarche and increased adrenocorticotropin-stimulated delta 5-steroid levels.

Abstract: Classic 3 beta-hydroxysteroid dehydrogenase (3 beta HSD) deficiency congenital adrenal hyperplasia (CAH) results from a mutation in the type II 3 beta HSD gene encoding adrenal and gonadal 3 beta HSD. We investigated the type II and type I 3 beta HSD gene sequences in 15 infants and children with premature pubarche (PP; mean/range of age at PP, 4/0.08-9 yr) and elevated ACTH-stimulated delta 5 precursor steroid levels. Compared to Tanner I control subjects of similar age, ACTH-stimulated hormonal levels were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Boys with PP were included in the study, if PP was attributable to premature adrenarche, as suggested by elevated serum concentrations of androstenedione (Δ 4 -A) and/or dehydroepiandrosterone sulfate (DHEAS) at prepubertal diagnosis of PP [15]and by lack of evidence for nonclassic adrenal hyperplasia (serum 17-OHP and 17-hydroxypregnenolone measurements after adrenocorticotropic hormone – ACTH – administration) [16, 17]and for precocious puberty (testicular volume at PP diagnosis ≤2 ml). None of the subjects had acanthosis nigricans, thyroid dysfunction, Cushing’s syndrome, hyperprolactinemia, or a family or personal history of diabetes mellitus.…”
Section: Methodsmentioning
confidence: 99%
“…Boys with PP were included in the study, if PP was attributable to premature adrenarche, as suggested by elevated serum concentrations of androstenedione (Δ 4 -A) and/or dehydroepiandrosterone sulfate (DHEAS) at prepubertal diagnosis of PP [15]and by lack of evidence for nonclassic adrenal hyperplasia (serum 17-OHP and 17-hydroxypregnenolone measurements after adrenocorticotropic hormone – ACTH – administration) [16, 17]and for precocious puberty (testicular volume at PP diagnosis ≤2 ml). None of the subjects had acanthosis nigricans, thyroid dysfunction, Cushing’s syndrome, hyperprolactinemia, or a family or personal history of diabetes mellitus.…”
Section: Methodsmentioning
confidence: 99%
“…All subjects were receiving a standard Mediterranean diet; none presented evidence for thyroid dysfunction, hyperprolactinemia, a family or personal history of diabetes mellitus, late-onset congenital adrenal hyperplasia [26, 27]; none was receiving an oral contraceptive treatment or a medication known to affect gonadal function or carbohydrate metabolism.…”
Section: Methodsmentioning
confidence: 99%